CGIAR Climate Community of Practice Launch, 12 April 2024, 9am session - CGIAR Climate Change Impact Platform (CGIAR System Organization, 2024)
The Climate Adaptation and Mitigation Impact Area Platform was established in 2023, marking its official launch with the appointment of a full-time Climate Platform Director in March of that year. Designed to streamline CGIAR's efforts to integrate cutting-edge science with strategic pathways for impact. The Climate Impact Area Platform is mandated to convene CGIAR’s climate scientists and synthesize climate research to enhance the capacity of CGIAR and its partners, amplify external visibility, engage with prominent climate voices, provide advice on portfolio-level management and strategy, and monitor the outcomes of various Initiatives.